Super selective dual nature GO bridging PSF-GOPebax thin film nanocomposite membrane for IPA dehydration - Mohamad Syafiq, Abdul Wahab; Sunarti, Abd Rahman; Rozaimi, Abu Samah (Taylor & Francis, 2020)
In this work, Graphene Oxide (GO) is embedded in both selective hydrophilic layer and porous hydrophobic substrate creating a mutual bridge between the two surfaces. Pristine 1–3 μm microporous PSF prepared via dry/wet phase inversion techniques with contact angle of 74.12° has been further study with GO embedded Pebax dense selective layer. This dual nature thin film nano composite TFNC membranes managed to reduce the water contact angle down to 37.18°. As for the IPA dehydration study, the total flux up to 1.19 kgm−2h−1 and 0 wt% IPA detected in permeate was achieved with 20 wt% water feed at 30°C.